Influence of thickness on tunability performance of plasma sputtered indium tin oxide as Q-switcher - Zalkepali,, N U H H; Mahmud, N A Awang, N N H E N; Muhammad, N A M; Zamri, A Z M (IOP, 2023)
We successfully investigated the influence of thickness on the tunability performance of plasma-sputtered indium tin oxide (ITO) as a Q-switcher. ITO is coated using direct current magnetron sputtering techniques with sputtering times of 150 s, 250 s, and 350 s to generate excellent quality ITO. Filmetrics measures the thickness, yielding 17.80 nm, 30.70 nm, and 38.90 nm, respectively. A stable Q-switched pulse is achieved at an operating wavelength and peak power of 1562.30 nm and −6.47 dBm for the thickness of 17.80 nm, 1561.40 nm and −3.19 dBm for the thickness of 30.70 nm, and 1560.2 nm and −2.44 dBm for the thickness of 38.90 nm. The thickness of 38.90 nm exhibit a high repetition rate of 43.60 kHz and narrow pulse width of 4.83 µs compared to other thickness. Employing the tunable bandpass filter in the laser ring cavity gives the wide-tuning of the wavelength range of 19.69 nm, 31.86 nm, and 36.59 nm for the thickness of 17.80 nm, 30.70 nm, and 38.90 nm, respectively. The tunability of Q-switched with the thicknesses of 30.70 nm and 38.90 nm is realized in the region of C-band to L-band. Regarding the authors’ expertise, this seems to be the first proposed influence of thickness on the tunability of plasma sputtered ITO that serves as saturable absorber in a Q-switched pulse.